How does global literacy affect environmental behavior? The mediating role of eco-anxiety - Bulut, Birol; Oksuzo, Muhammed Kursat (Resilience Alliance, 2026)
. The asymmetric relationship between humans and nature and the escalating ecological crises have revealed the need for a profound transformation in individuals' perceptions, attitudes, and behaviors toward the environment. In this transformation process, teacher education plays a key role in cultivating individuals who understand life as a web of interdependence and who develop an ethical sense of responsibility and respect for nature. In this regard, understanding the processes through which preservice teachers- who will become the primary agents of future social transformation-develop global awareness, eco-anxiety, and pro-environmental behaviors is of great importance. Accordingly, this study aims to examine the effect of preservice teachers' levels of global literacy on their environmental behaviors and to determine whether this relationship operates indirectly through eco-anxiety. Using a cross-sectional survey design, one of the quantitative research methods, the study was conducted with 660 preservice teachers enrolled in nine undergraduate programs at the Faculty of Education of a public university in Turkey. Data were collected through the Global Literacy Scale, the Hogg Eco-Anxiety Scale (HEAS-13), and the Environmental Behavior Scale. The fit between the theoretically proposed model and the data was evaluated using structural equation modeling (SEM) with the maximum likelihood estimation method. In addition, a bootstrapped path analysis was performed to determine whether eco-anxiety served as a mediating variable in the relationship between global literacy and environmental behavior. The results indicated that the model had an acceptable level of fit (Chi 2/df = 2.00, RMSEA = 0.039, SRMR = 0.062, CFI = 0.90). Global literacy exerted a strong and statistically significant direct effect on environmental behavior and a small yet significant indirect effect through eco-anxiety. Together, global literacy and eco-anxiety accounted for 37% of the variance in environmental behavior. Although global literacy explained only 2% of the variance in eco-anxiety, eco-anxiety acted as a constructive emotional catalyst, strengthening this relationship and translating global awareness into action. The study positions eco-anxiety as a psychological bridge between cognitive awareness and environmental action, thus offering a theoretical contribution to the knowledge-attitude-behavior model. Practically, the findings highlight the need to integrate global literacy and emotional resilience training into teacher education programs.
Keywords: eco-anxiety; environmental behavior; global literacy; preservice teachers; pro-environmental behavior